IMPLEMENTASI MEDIA VISUAL DALAM PENDIDIKAN AGAMA KATOLIK UNTUK MENINGKATKAN MINAT BELAJAR SISWA DI SEKOLAH MENEGAH ATAS RK DELIMURNI DISKI KELAS XI - Lumbanbatu, Johannes Sohirimon; Tarigan, Leo (IN VERITATE LUX, 2022)
This research aims to look at the implementation of visual media in Catholic religious education to increase students' interest in learning in class XI RK Delipuri Diski high school. The background to this research stems from the fact that many teachers still teach using the story method so that learning becomes boring and students lack interest in learning. This research uses a qualitative approach. Research data was obtained by observation, interviews and documentation. The research targets were Catholic Religious Teachers and students at RK Deliwarni Diski High School. This research aims to determine the implementation of visual media in Catholic religious education and determine students' learning interests. The research results show that the implementation of visual media has been carried out well in the school and is able to foster students' interest in learning